2018
DOI: 10.2136/vzj2018.11.0207
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Soil Physics for Securing Food, Water, Soil and Ecosystem Services

Abstract: Core Ideas Contributions are mainly from the 2017 International Soil Physics Workshop in China. Soils are fundamental in supplying food, energy, water (FEW), and ecosystem services. Interdisciplinary (convergence) approaches are needed to address FEW challenges. Soils are foundational to sustaining the food, energy, and water (FEW) systems and provide many essential ecosystem services. Soil degradation is a major threat to food security in China and elsewhere in the world. It is critical to advance soil scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…A laboratory test of the water drop penetration time (DeBano, 1981;Doerr et al, 2000) on a soil sample of the upper soil material showed that the organic layer is highly water repellent in dry conditions (air dried for 2 weeks; water drop penetration time > 10 min). An increase in the hydrophobicity index (Tillman et al, 1989) with increasing moraine age was also found by Maier et al (2019). Thus, we conclude that the hydrophobicity of the organic top layer has a big impact on infiltration and the initiation of unstable flow.…”
Section: Intermediate Stage: 3000 Yearssupporting
confidence: 65%
See 2 more Smart Citations
“…A laboratory test of the water drop penetration time (DeBano, 1981;Doerr et al, 2000) on a soil sample of the upper soil material showed that the organic layer is highly water repellent in dry conditions (air dried for 2 weeks; water drop penetration time > 10 min). An increase in the hydrophobicity index (Tillman et al, 1989) with increasing moraine age was also found by Maier et al (2019). Thus, we conclude that the hydrophobicity of the organic top layer has a big impact on infiltration and the initiation of unstable flow.…”
Section: Intermediate Stage: 3000 Yearssupporting
confidence: 65%
“…The ability of soil to store and to transport water is essential for its ecosystem services such as nutrient cycling or water and gas balances (Clothier et al, 2008;Amundson et al, 2015;Hatfield et al, 2017;Shang et al, 2018). Thus, the interaction of water and soil is an elementary foundation for the existence and functioning of terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to reduced BD from long-term continuous cropping systems which increased annualized crop yields in contrast to increased BD from crop-fallow systems which increased BD but lowered annualized crop yields. Many researchers 15 , 17 , 27 reported that BD was negatively related to crop yield. However, Logsdon and Karlen 2 demonstrated that BD had no effect on crop yield.…”
Section: Discussionmentioning
confidence: 99%
“…Sene et al 14 found that sand concentration and SHC were positively correlated, but soil aggregation was negatively correlated to crop yield. Shang et al 15 reported that soil water content and aggregate stability (AS) were positively related, but BD was negatively related to crop yield. Similarly, several researchers 16 , 17 observed that BD was negatively related to crop yield.…”
Section: Introductionmentioning
confidence: 99%